Kairos fotografii – moment i wartość - Spalińska-Mazur, Joanna (Annales Universitatis Paedagogicae Cracoviensis | Studia de Cultura, 2014)
Kairos of photography - the moment and value Since we have handed over the manufacturing process to machines, the art-photography reaches the limit where creation is identified with cropping. The article essentially focuses on works by Georges Rousse, who can hardly be placed in the indicated paradigm and who often declares that his painting interventions in places of different architecture result from his drive for sanctification of the places that may disappear or become empty. In case of this type of activities, we are not dealing with the reflection of the actual history of the places or a narrative that can be presented, but with the exploration of the possible time orders - not so much logical as imaginary; we are dealing with a higher register of sensations - with heterotopia. Geometric and monochromatic paintings that Rousse creates, based on simple architectural patterns to better modify the perception, disappear along with the places that contain them. The explosive moment of this art-photography, its kairos, urges the audience to learn the mystery of the documented places; to travel in search of their original shape and energy.